Cultural Aspects of Character Education found in Comic "Pelayaran Ke Dusung": An Ecranization through the Application of Augmented Reality - Suma, Mansyur; Rahman, Fathu; Dalyan, M.; ., Zakaria; Andini, Citra; Wajadi, Andi Muh. Farid (Journal of Ecohumanism, 2024)
This research examines the cultural aspects of character education portrayed in Firdaus' comic, "Pelayaran Ke Dusung," which was nominated for a festival award. This comic has undergone the process of screen adaptation (ekranisasi) from the Epic I La Galigo with the main character, Sawerigading. To bring this comic closer to readers, it can be accessed through an Augmented Reality (AR) application. This approach aims to preserve the moral character values contained in the Epic I La Galigo. The objectives of this research are 1) to actualize thematic stories with local content that are relevant to actual life, and 2) to preserve the cultural values found in the comic "Pelayaran ke Dusung," which is popular among Gen Z. The results of this research show that comics with reflections or guidance on how the taught values can be implemented in real life provide a strong message, empowering readers to practice the values of Sipakatau, Sipakalebbi, and Sipakainge in their daily lives. In addition to developing AR-based comics, this research also conducts a comprehensive evaluation of the effectiveness of utilizing AR for comics. This not only focuses on technical aspects such as visual quality and interactivity but also on its impact on understanding and internalizing the traditional Bugis character values among the younger generation. The implications of this research are expected to provide empirical evidence regarding the potential of AR in bringing traditional values to life and making it more relevant and engaging for the younger generation.